ChemInform Abstract: Two‐Component Domino Reactions Initiated from Ketenes: Serendipitous Synthesis of Quinolizidinones Analogous to Chelated Lobeline′s Conformation. Issue 8 (February 2016) - Drege, Emmanuelle; Venot, Pierre‐Etienne; Le Bideau, Franck; Retailleau, Pascal; Joseph, Delphine
Abstract: A highly diastereoselective one‐pot procedure for the quinolizidinone synthesis from norlobelanine is described.